Go-with words - Dobkin, Bonnie; Dunnington, Tom (Chicago : Childrens Press, 1993)
Rhyming text presents related words, such as short and long, page and book, and night and moon.
1.5
2.
K-3
P-2.
Keywords: Vocabulary -- Juvenile literature; Vocabulary; Vocabulary; Readers (Elementary).